Respons Beberapa Varietas Bawang Merah (Allium Ascalonicum L.) Asal Biji Botani Pada Populasi Tanaman yang Berbeda - Putra Utama; Anisa Fitriani; Alfu Laila; Abdul Hasyim Sodiq; Kartina Kartina (Jurnal Agroekoteknologi, 2023)
This research aimed to determine the effect of several varieties on different populations on the growth and yield of shallot (Allium ascalonicum L.) from botanical seeds (True Shallot Seed). This research was an experimental research conducted from August to October 2021 in the integrated farming system area, Serang, Banten. This research was laid out in a factorial randomized block design (RCBD) consisting of two factors. The first factor was the differences in varieties consist of 3 levels, namely Maserati (v1), Sanren (v2), and Tuk-Tuk (v3). The second factor was the population which consists of 4 levels, namely the population of 1 plant (p0), 2 plants (p1), 3 plants (p2), and 4 plants (p3). The results showed that there was an interaction between the varieties and populations on the parameters of fresh weight of bulbs/plant, the combination of Maserati variety with 1 population (40.32g). The Sanren variety gave the best effect on the parameters of bulbs/plant (1.92 bulbs).  Keyword : Population, Shallot, Varieties